User‐centered approaches in software development processes: Qualitative research into the practice of Hungarian companies. Issue 2 (25th August 2022) - Szabó, Bálint; Hercegfi, Károly
Abstract: Integrating user‐centered approaches into development processes is one of the main challenges nowadays that derives from different objectives of software engineering (SE) and human‐computer interaction (HCI) fields. For SE experts, the main goal is quality code creation, whereas for HCI professionals, it is the continuous product interaction with the users. The major question is what tools and timings can be used together to achieve these goals effectively. Therefore, this article provides comparative, exploratory, and qualitative research about possible solutions on how practitioners transfer HCI values and practices to SE processes. The current practice of software companies was studied by conducting interviews on a sample of 13 Hungarian Information Technology companies to explore the SE processes in respect of several dimensions (applied development models, the integrity of user‐centered methods, and the user experience [UX] maturity). According to preliminary expectations, the development processes of the various companies proceed in different steps; nevertheless, they can be well grouped together based on the UX methods applied. The results representing the various user‐centered processes can be considered useful for future decision makers of software companies worldwide. Abstract : Integrating user‐centered approaches into development processes is one of the main challenges nowadays that derives from different objectives of software engineering (SE) and human‐computer interaction (HCI) fields. Therefore, this article provides comparative, exploratory, and qualitative research about possible solutions on how practitioners transfer HCI values and practices to SE processes. The results representing the various user‐centered processes can be considered useful for future decision makers of software companies worldwide.